PENGARUH LAMA FERMENTASI TERHADAP KADAR BIOETANOL DARI LIMBAH KULIT PISANG KEPOK DAN RAJA - Arifani Bestari; Endro Sutrisno; Sri Sumiyati (Jurnal Teknik Lingkungan, 2013)
Banana peel (musa sapientum) is organic waste that have value of carbohydrates that high and nutrition that can help the growth of a microbe. Based on it, then appears an idea to make use of the  bioethanol from the peel as a source of raw materials. Bioethanol is one alternative energy that are spoken currently who is expected to replace energy source of petroleum that has existed that is the fluid a result fermentation of sugar from sources of carbohydrate used the aid microorganisms. In this research process of waste the banana peel become bioethanol is aimed to determine the process of waste the banana peel plantain and kepok, ranging from process of smoothing the hydrolysis of, fermentation until distillation of which are then analyzed levels of each  bioetanol each kind of the banana peel based on the number of yeast and time. In this process of fermentation by the addition of saccharomyces cerevisiae by  number of yeast, as many as 3 5, 7 gram with long  fermentation different namely during 2, 4, 6, 8 days influencing the outcome of the level of bioethanol on the type of skin of plantain and kepok. This result of research produce levels of bioethanol the most high that is on the type of kepok banana peel with yeast fermentation as many as seven gram during the time of 8 days worth 17.05 % while on the peel of plantain with heavy yeast and the same time having bioetanol levels as many as 16.55 %. The longer fermentation, microorganisms more active and the extension of yeast the result of ethanol is increasing contained in a sample of the banana peel with heavy yeast 3, 5 grams, 7 gram levels of ethanol more robust on the day to  8.